nseignement de la traduction médicaleStratégie, difficultés et propositions - Mohammedi, Leila (جامعة وهران 1 أحمد بن بله - مخبر تعليمية الترجمة وتعدد الألسن, 2015)
Nations' development can be measured by the reliable criterion of scientific translation. Science and translation are two sides of the same coin, since they have lot of related feautures that cannot be dissociated. On an other hand, medical translation is part and parcel of scientific translation, because the first borrows from the latter its method, the way of constructing terminology, the great difficulty of style, of expressions, etc… Our communication deals with teaching medical translation in Algeria. This field didn't receive the attention it deserves under the classical system. Fortunately, under the current L.M.D. System, we have the opportunity to teach specialized translation, among which medical translation. The objective is to try to form qualified and efficient medical translator who will be able to translate all types of médical documents and to achieve a successfull specialized work.
تعد الترجمة العلمية معيارا موثوقا به لمعرفة مدى تقدم الأمم. فالعلم والترجمة وجهان لعملة واحدة لا يمكن الفصل بينهما، كما أن العلاقة بينهما طردية. والحديث عن الترجمة العلمية عادة ما يقودنا للحديث عن الترجمة الطبية لما لهذه الأخيرة من مميزات العلم كطبيعة ميدان التخصص، ومصطلحاته، ونوعية عباراته وتراكيبه، وصعوبته وغيرها. من هذا المنطلق ارتأينا التطرق لتدريس الترجمة الطبية في الجزائر كونه لم يحظ بالاهتمام الكبير في النظام الكلاسيكي. وبالتالي فنظام (ل.م.د) فرصة سانحة للتركيز على تدريس الترجمة الطبية لتكوين مترجمين متخصصين أكفاء قادرين على تأدية مهام المترجم الطبي بثقة كبيرة نظرا لما يتلقونه من تدريب مكثف في الميدان الطبي والترجمي على حد سواء. إذ ستتم مقارنة تدريس الترجمة الطبية في الجزائر بما يقدم في معاهد أجنبية، ويلي هذا اقتراح لاستراتيجية لتدريس هذا النوع من الترجمة في الجزائر، وإشارة للحلول التي يتبناها الأستاذ لتمكين المترجم المتمرن من تجاوز الصعوبات.
Keywords: علم الطب -- الاطباء -- الترجمة الطبية -- المصطلحات الطبية -- المعاجم العلمية -- البحوث الطبية -- مستخلصات الأبحاث -- الترجمة -- اللغات الأجنبية